Evaluation of the impact of hypoxic conditions on the viability of spermatozoa after capacitation and cryopreservation - Klymukhina, Olga; Petrushko, Maryna (Problems of Cryobiology and Cryomedicine, 2025)
Probl Cryobiol Cryomed 2025; 35(4):245